Dietary Silicon Deficiency Does Not Exacerbate Diet-Induced Fatty Lesions in Female ApoE Knockout Mice. Issue 7 (13th May 2015) - Jugdaohsingh, Ravin; Kessler, Katharina; Messner, Barbara; Stoiber, Martin; Pedro, Liliana D; Schima, Heinrich; Laufer, Günther; Powell, Jonathan J; Bernhard, David
Abstract: Background: Dietary silicon has been positively linked with vascular health and protection against atherosclerotic plaque formation, but the mechanism of action is unclear. Objectives: We investigated the effect of dietary silicon on 1 ) serum and aorta silicon concentrations, 2 ) the development of aortic lesions and serum lipid concentrations, and 3 ) the structural and biomechanic properties of the aorta. Methods: Two studies, of the same design, were conducted to address the above objectives. Female mice, lacking the apolipoprotein E ( apoE ) gene, and therefore susceptible to atherosclerosis, were separated into 3 groups of 10–15 mice, each exposed to a high-fat diet (21% wt milk fat and 1.5% wt cholesterol) but with differing concentrations of dietary silicon, namely: silicon-deprived (−Si; <3-μg silicon/g feed), silicon-replete in feed (+Si-feed; 100-μg silicon/g feed), and silicon-replete in drinking water (+Si-water; 115-μg silicon/mL) for 15–19 wk. Silicon supplementation was in the form of sodium metasilicate (feed) or monomethylsilanetriol (drinking water). Results: The serum silicon concentration in the −Si group was significantly lower than in the +Si-feed (by up to 78%; P < 0.003) and the +Si-water (by up to 84%; P < 0.006) groups. The aorta silicon concentration was also lower in the −Si group than in the +Si-feed group (by 65%; P = 0.025), but not compared with the +Si-water group. There were no differences in serum and aorta silicon concentrations between the silicon-replete groups. Body weights, tissue wet weights at necropsy, and structural, biomechanic, and morphologic properties of the aorta were not affected by dietary silicon; nor were the development of fatty lesions and serum lipid concentrations. Conclusions: These findings suggest that dietary silicon has no effect on atherosclerosis development and vascular health in the apoE mouse model of diet-induced atherosclerosis, contrary to the reported findings in the cholesterol-fed rabbit model.